Optimal Monetary Policy in a Currency Union: Implications of a Country-specific Cost Channel - Jochen Michaelis; Jakob Palek (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
There is growing empirical evidence that the strength of the cost channel of monetary policy differs across countries. Using a New Keynesian model of a two-country monetary union, we show how the introduction of a cost channel (differential) alters the optimal monetary responses to union-wide and national shocks. The cost channel makes monetary policy less effective in combating inflation, but it is shown that the optimal response to the decline in effectiveness is a stronger use of the instrument. On the other hand, the larger the cost channel differential, the less aggressive will the optimal monetary policy be. For almost all para- meter constellations, our welfare analysis suggests a clear-cut ranking of policy regimes: commitment outperforms the Taylor rule, the Taylor rule outperforms strict inflation targeting, and strict inflation targeting outperforms discretion.
Keywords: E31; E52; F41; 330; cost channel; optimal monetary policy; monetary union; open economy macroeconomics